Rolling Back the Public Sector - Differential Effects on Employment, Investment and Growth - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2003)
The macroeconomic effects on growth, investment and private sector employment of different ways of rolling back the welfare state are analysed. Cutting public spending on private goods induces a lower interest rate, a higher wage, a lower capital stock and a fall in employment. Cutting public employment or the income tax rate leads, in contrast, to a lower wage, a higher interest rate and a higher capital stock. Employment rises on impact. If the extra revenues of rolling back the welfare state are handed back via a lower income tax rate rather than a lump-sum subsidy, both cutting public employment and cutting public spending on private goods induce an investment boom. Making the tax system less progressive by cutting tax credits and the income tax rate induces an investment boom as well. The effects of endogenous growth, adjustment costs for investment and non-competitive labour markets are considered as well
Keywords: 330; welfare state; public employment; labour market; investment; economics growth